Spatial reflexivity and undergraduate transitions in the Republic of Ireland after the Celtic Tiger - Cairns, D.; K. Growiec; Smyth, J. (Journal of Youth Studies, 2012)
This article explores the geographical mobility intentions of students aged between 18 and 24 years in the Republic of Ireland after the end of the economic boom commonly referred to as the ‘Celtic Tiger’. Focusing upon a sample of undergraduates in Dublin and Cork, the article looks at how many respondents intend to move abroad in the future, where the potential leavers intend to go and for how long they envisage staying away, in addition to elaborating mobility decision-making processes. Results show that 59% had plans for to leave, largely to English language speaking destinations, with most sojourns envisaged as temporary. The evidence also suggests that more young women than young men are seeking an exit and that a wide range of factors can influence mobility decision-making, most prominently personal development and friendship ties, but not economic fears. The concluding discussion considers the meaning of these outcomes for these young people and the potential significance of spatial reflexivity in transitions from education to work, particularly in an economic crisis context.